Efeito da restrição alimentar no desempenho reprodutivo de machos de matrinxã Brycon cephalus - Sanabria Ochoa, Ana Isabel [UNESP] (Universidade Estadual Paulista (Unesp), 2002)
The present study was performed in the Aquaculture Center of the University of São Paulo State, Jaboticabal, SP. Two experiments evaluated the effect of moderate and alternate food restriction on seminal characteristics and reproductive performance of matrinxã (Brycon cephalus). In the first experiment, adult males were distributed into 2 groups. One of them received ration daily (G1, control) and the other (G2, experimental) was fed alternately (fed 3 for days, starved 2 for days) for 3 months during the gonadal maturation. Each group was allotted into 2 earthen ponds (10 fish each) and after 3 months of treatment, males were induced to reproduction with carp pituitary extract (CPE) (1 mg kg-1). After 150 hour/degree, the males were anesthetized (benzocaine, 0.1g/L-1) and semen from each fish were collected by abdominal massage to measure the volume and the spermatocrit in capillary tubes. After that, through microscopy, the cell motility, number of live cells and cell concentration in Neubauer Chamber were determined. A fertilization test was also performed utilizing oocytes from one single female fed daily and CPE induced. Oocytes were divided into 14 samples and fertilized with semen from every male individually. They were incubated in 20L plastic boxes under constant water aeration. Fertilization rate was determined 7 h after fertilization. Hatching rate was also registered and larvae were observed until the yolk sac resorption (72 h after hatching), being collected and fixed to weight and length measurement. Spermatic volume was higher in G2 (9.29 ± 3.31 ml) than in G1 (6.14 ± 1.10 ml), while the motility was similar in both groups (5.00). Cell concentration were also similar in both treatments (6.79 ± 1.16 and 6.65 ± 1.37 cell 106 μL-1, in G1 and G2, respectively), as well as the spermatocrit (13.07 ± 1.99 % in G1 and 13.86 ± 2.87 % in G2). Live cells number did not differ ...

Este trabalho foi realizado no Centro de Aqüicultura, Universidade Estadual Paulista, Câmpus de Jaboticabal-SP. Foram feitos 2 experimentos para avaliar o efeito da restrição alimentar moderada e alternada nas características seminais do matrinxã (Brycon cephalus) e no seu desempenho reprodutivo. No primeiro experimento, utilizaram-se machos adultos distribuídos em 2 grupos, sendo que um (G1, controle) recebeu ração diariamente ad libitum, e o outro (G2, experimental) foi alimentado de forma alternada (3 dias de alimentação e 2 dias de restrição) por três meses, no período da maturação final dos gametas. Cada grupo foi distribuído em 2 viveiros, com 10 animais em cada. Terminados os tratamentos, os machos foram induzidos à reprodução com extrato pituitário de carpa (EPC) (1,0 mg kg-1). Após 150 horas/grau, os machos foram anestesiados (benzocaína, 0.1g*L-1) e foi coletado o fluido seminal individualmente, por massagem abdominal. Após medido o volume, sêmen foi coletado em tubos capilares para determinação do espermatócrito. Posteriormente, foram avaliadas a motilidade, porcentagem de células vivas e mortas e concentração espermática em câmara de Neubauer. A seguir, realizou-se um teste de fertilização, utilizando óvulos de uma fêmea alimentada diariamente e induzida com EPC. Os óvulos foram divididos em 14 alíquotas e fertilizados com sêmen de cada um dos machos utilizados no estudo, sendo incubados em caixas plásticas com 20 L de água e aeração constante. A porcentagem de fertilização foi calculada 7 horas pós-fertilização. A taxa de eclosão também foi registrada e as larvas obtidas foram observadas até a reabsorção do saco vitelino (72 horas pós-eclosão), sendo coletadas e fixadas a cada 24 horas, para medida de peso e comprimento. O volume espermático foi maior em G2 (9,29 ± 3,31 ml) que em G1 (6,14 ± 1,10 ml), enquanto que a motilidade...
Keywords: Peixe; Peixe - Reprodução; Peixe - Nutrição; Restrição calórica; Desempenho; Fishes